SYSTEMATIC ASSESSMENT WITH “POE” METHOD IN OFFICE BUILDINGS CASES STUDY ON THE REDESIGN RESULTS OF OFFICE INTERIOR AFTER OCCUPIED AND OPERATED - Permana, Asep Yudi; Nurrahman, Hafiz; Salsabilla Permana, Aathira Farah (Journal of Applied Engineering Science, 2021)
An office is a center of operations where various activities take place, depending on the business conducted. Office conditions determine the credibility and synergy of business entity, as well as the officers' performance and productivity. This study formulates an interior design concept based on the Post Occupancy Evaluation (POE), with Mixed Methods Research (MMR) approach, which emphasizes the empirical meaning based on relevant field data. The research object is the Haleyora Powerindo (HPI) office building in Jakarta. MMR approach ensures the significance level of the work environment quality in the room and the workplace, as well as the officers' performance. The first step was analyzing the spatial conditions in the field based on standardization, which was conducted according to the satisfaction survey of officers. The results show that the work environment quality is high and responds positively. According to the workplace quality, satisfaction is mainly related to workspace area and quality, comfort and style of furniture, circulation, and accessibility to the work table, effectiveness and efficiency of workplace layout, ICT implementation, and HVAC and maintenance. Social space and entertainment facilities provide flexibility in interacting between officers of different divisions that were not in the previous office. Based on the results of multiple regression calculations, the in-door environment (IEQ) and the officer workspace (WQ) quality have a significant effect on officer performance (OP). These are 3 main factors critical in conducting systematic evaluations to obtain results from office space design. This study is expected to be a strategic reference for planning and designing a similar spatial atmosphere in different locations or cases
Keywords: in-door environment quality; workspace quality; officer performance; comfort and style of furniture; circulation; social space; flexibility